Phenomenology of Perception - Merleau-Ponty, Maurice; Smith, Colin (London Taylor & Francis, 2002)
Challenging and rewarding in equal measure, Phenomenology of Perception is Merleau-Ponty's most famous work. Impressive in both scope and imagination, it uses the example of perception to return the body to the forefront of philosophy for the first time since Plato. Drawing on case studies such as brain-damaged patients from the First World War, Merleau-Ponty brilliantly shows how the body plays a crucial role not only in perception but in speech, sexuality and our relation to others.
Keywords: 20th Century (1901-2000); Philosophy; Phenomenology; France